ANALISIS PENETAPAN ‘KETENGBAN’ SEBAGAI DAERAH OTONOM BARU DARI WILAYAH PEGUNUNGAN BINTANG - Gire, Emius; Julison, Bernathius; Bachtiar, Petrus (Magister Perencanaan Wilayah dan Kota Universitas Cenderawasih, 2023)
The purpose of the study was to analyze the determination of 'Ketengban' as a New Autonomous Region from the Bintang Mountains Region. The type of research used is descriptive qualitative. Data collection techniques are interviews, observation, and documentation. Data analysis techniques: Data reduction, Data presentation, Drawing conclusions or verification. The results of his research, first It is necessary to establish a new autonomous region from the Bintang Mountains Region, implemented by the provisions of the Unitary State of the Republic of Indonesia having regulations governing regional government by the mandate of the 1945 Constitution, the government shall enact Law Number 2 of 2021 as a replacement for Law Number 21 of 2001 on special autonomy for Papua Province. Second Matter that concerns the stipulation of 'Ketengban' as a New Autonomous Region from the Bintang Mountains Region that is carried out by the regulations can be seen in the Brief Report of the Commission II DPR RI public hearing meeting which has stated that the DPRD and the Regional Government of the Bintang Mountains Regency submitted administrative completeness submitted to Commission II of the DPR RI. Third, What benefits can be obtained from the stipulation of 'Ketengban' as a New Autonomous Region, which can be seen in improving the standard of living and welfare of the community, Gunung Bintang Regency, Papua Province? In addition, the Bintang Mountains of Papua Province, in developing or developing their regions, are experiencing an accelerated increase.